Kierunki dyfuzji wiedzy w małej firmie - Stosik, Aneta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the article the problem of knowledge management in Polish small business is presented. The article includes reflections about changing directions of modern organizations with effective human resources management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 259-267